1995
DOI: 10.1108/09596119510146751
|View full text |Cite
|
Sign up to set email alerts
|

The balanced score‐card: short‐term guest or long‐term resident?

Abstract: One recently developed performance measurement method which may prove more effective for hotel management is that of the “balanced score‐card” – which aims to give management a “comprehensive but quick” view of their organization′s performance. Investigates whether the “score‐card” may represent a long‐term solution to the “superior performance measurement method” the hotel sector is apparently looking for – or whether it is more likely to be just a short‐term, passing fad?

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
48
0

Year Published

1996
1996
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(48 citation statements)
references
References 6 publications
0
48
0
Order By: Relevance
“…Most organizations rely exclusively on financial performance measures to assess organizational performance (Neely, 1999;Hoque & James, 2000). Critics have argued that these measures are excessively profit-based (Brander Brown & McDonnell, 1995), short-term (Denton & White, 2000), unbalanced (Harris & Mongiello, 2001), unsatisfactory for businesses seeking a competitive advantage (Phillips, 1999;Evans, 2005), past oriented (Atkinson & Brander-Brown, 2001), little market oriented (Phillips & Louvieris, 2005), inadequate for strategic decisions (Kaplan & Norton, 1992), unable to measure value created, unable to measure intangible assets (Norreklit, 2000;Giannetti, Marelli & Vitali, 2002) and nonholistic (Phillips, 1999) and therefore, over reliance on them is no longer appropriate for today's managers.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Most organizations rely exclusively on financial performance measures to assess organizational performance (Neely, 1999;Hoque & James, 2000). Critics have argued that these measures are excessively profit-based (Brander Brown & McDonnell, 1995), short-term (Denton & White, 2000), unbalanced (Harris & Mongiello, 2001), unsatisfactory for businesses seeking a competitive advantage (Phillips, 1999;Evans, 2005), past oriented (Atkinson & Brander-Brown, 2001), little market oriented (Phillips & Louvieris, 2005), inadequate for strategic decisions (Kaplan & Norton, 1992), unable to measure value created, unable to measure intangible assets (Norreklit, 2000;Giannetti, Marelli & Vitali, 2002) and nonholistic (Phillips, 1999) and therefore, over reliance on them is no longer appropriate for today's managers.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Harris & Mongiello (2001) and Doran et al (2002) examined the range of key indicators that hotel managers find useful in managing their businesses, acknowledging the value of the BSC. Brander-Brown & McDonnell (1995), Phillips (1999), Atkinson & Brander-Brown, (2001), Ittner et al (2003), Banker, Potter & Srinivasan (2005), Haktanir & Harris (2005) and Ramdeen, Santos & Chatfield (2007) concluded that both financial and non-financial performance improve the overall performance of organizations. Other studies including that of Evans (2005) in the United Kingdom, Huang et al (2007) and Chen et al (2011) in China, Bergin-Seers & Jago (2007) in Australia, Min et al (2008) and Kim & Lee (2009) in Korea, Pavlatos & Paggios (2009) in Greece, Ivankovic et al (2010) in Slovenia and Eldeeb (2011) in Egypt confirmed the successful application of BSC as a performance measurement system in hospitality organizations.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The traditional performance dimensions and indicators used by the management of hotels such as occupancy percentages, profit indicators and return on investment are invalid in competitive business environment (Brown & McDonnell, 1995). In contemporary management it is argued the business performance is the outlook of strategic management, which is a subset of the overall organizational effectiveness, includes financial, operational and organizational performance i.e.…”
Section: Organisation Performance In Hotel Industrymentioning
confidence: 99%
“…Brander et al (1995) report a pilot study undertaken at a five-star hotel. In doing so, they identify the objectives of that organization and how particular measures were developed to monitor business performance.…”
mentioning
confidence: 99%